Uncovering the connection between ceiling height and emotional reactions in art galleries with editable 360-degree VR panoramic scenes - Zhang, Zhihui; Fort, Josep M.; Giménez Mateu, Lluis; Chi, Yuwei (Frontiers in Psychology, 2023)
This study investigates the relationship between ceiling height and emotional responses in art galleries using editable 360-degree VR panoramic scenes. While previous research has explored the influence of spatial dimensions on general positive and negative emotions, the specific impact of ceiling height in art gallery settings, particularly on discrete emotions, remains understudied. Employing an experimental design, we presented 183 participants with virtual art gallery environments featuring varying ceiling heights and assessed their emotional responses through self-report measures. The data revealed a pronounced influence of ceiling height on particular emotions, notably disgust and joy, while its effect on emotions such as fear, anger, sadness, and surprise was more subdued. Beyond its primary findings, this research underscores the efficacy of editable 360-degree panoramic photo scene modeling in environmental psychology studies within virtual reality contexts.